A Simple and Efficient System for Regulating Gene Expression in Human Pluripotent Stem Cells and Derivatives. (17th April 2014) - Qian, Kun; Huang, CindyTzu‐Ling; Chen, Hong; Blackbourn, Lisle W.; Chen, Yuejun; Cao, Jingyuan; Yao, Lin; Sauvey, Cornall; Du, Zhongwei; Zhang, Su‐Chun
Abstract: Regulatable transgene expression in human pluripotent stem cells (hPSCs) and their progenies is often necessary to dissect gene function in a temporal and spatial manner. However, hPSC lines with inducible transgene expression, especially in differentiated progenies, have not been established due to silencing of randomly inserted genes during stem cell expansion and/or differentiation. Here, we report the use of transcription activator‐like effector nucleases‐mediated targeting to AAVS1 site to generate versatile conditional hPSC lines. Transgene (both green fluorescent protein and a functional gene) expression in hPSCs and their derivatives was not only sustained but also tightly regulated in response to doxycycline both in vitro and in vivo. We modified the donor construct so that any gene of interest can be readily inserted to produce hPSC lines with conditional transgene expression. This technology will substantially improve the way we study human stem cells. Stem Cells 2014;32:1230–1238